2017
DOI: 10.1007/s11126-017-9524-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ‘Being There’: Psychiatric Staff Attitudes on the Use of Restraint

Abstract: These findings highlight the importance of proximity of staff members to incidences of restraints. This may have implications in understanding the professional and social discourse concerning mechanical restraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
2
24
0
4
Order By: Relevance
“…Nurses who had closer contact with restraint methods were more likely to consider these methods as a manner of achieving security and care than nurses who did not have as many direct experiences of using restraint (Dahan et al . ). According to Wynn et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Nurses who had closer contact with restraint methods were more likely to consider these methods as a manner of achieving security and care than nurses who did not have as many direct experiences of using restraint (Dahan et al . ). According to Wynn et al .…”
Section: Resultsmentioning
confidence: 97%
“…Nurses who had closer contact with restraint methods were more likely to consider these methods as a manner of achieving security and care than nurses who did not have as many direct experiences of using restraint (Dahan et al 2017). According to Wynn et al (2011), staff appeared to be careful in their use of the maximum restrictive methods and preferred less restrictive methods whenever possible.…”
Section: Behavioural Component Of Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…Este concepto fue definido por Festinger en 1956 como la desarmonía interna o la incongruencia entre ideas, creencias o emociones y conducta. El profesional de enfermería (Cocho et al, 2018;Dahan, et al, 2017;Staniulienė et al, 2013) se dedica al cuidado holístico de la persona, haciéndola partícipe de sus propios cuidados y fomentando la autonomía, el hecho de aplicar la técnica de la contención mecánica a la persona que está cuidando puede entrar en conflicto con los códigos éticos de los propios profesionales de enfermería. Según la bibliografía consultada (Cocho et al, 2018;Dahan, et al, 201;Riahi et al, 2016;Staniulienė et al, 2013) existen diversos mecanismos para el alivio de la disonancia cognitiva que genera en el profesional de enfermería el utilizar medidas coercitivas.…”
Section: Discusión Vivencia Del Profesional De Enfermería Respecto a unclassified
“…Earlier research has also shown that gender and age are related to attitudes towards containment methods (Hottinen et al, 2012; Whittington, Bowers, Nolan, Simpson, & Neil, 2009). Previous involvement in restrictive situations is also related to greater acceptance of containment methods (Dahan et al, 2018; Whittington et al, 2009).…”
Section: Introductionmentioning
confidence: 99%